Home-based tuberculosis contact investigation in Uganda: a household randomised trial. Issue 3 (29th July 2019) - Davis, J. Lucian; Turimumahoro, Patricia; Meyer, Amanda J.; Ayakaka, Irene; Ochom, Emma; Ggita, Joseph; Mark, David; Babirye, Diana; Okello, Daniel Ayen; Mugabe, Frank; Fair, Elizabeth; Vittinghoff, Eric; et al.
Introduction: The World Health Organization (WHO) recommends household tuberculosis (TB) contact investigation in low-income countries, but most contacts do not complete a full clinical and laboratory evaluation. Methods: We performed a randomised trial of home-based, SMS-facilitated, household TB contact investigation in Kampala, Uganda. Community health workers (CHWs) visited homes of index patients with pulmonary TB to screen household contacts for TB. Entire households were randomly allocated to clinic (standard-of-care) or home (intervention) evaluation. In the intervention arm, CHWs offered HIV testing to adults; collected sputum from symptomatic contacts and persons living with HIV (PLWHs) if ≥5 years; and transported sputum for microbiologic testing. CHWs referred PLWHs, children <5 years, and anyone unable to complete sputum testing to clinic. Sputum testing results and/or follow-up instructions were returned by automated SMS texts. The primary outcome was completion of a full TB evaluation within 14 days; secondary outcomes were TB and HIV diagnoses and treatments among screened contacts. Results: There were 471 contacts of 190 index patients allocated to the intervention and 448 contacts of 182 index patients allocated to the standard-of-care. CHWs identified 190/471 (40%) intervention and 213/448 (48%) standard-of-care contacts requiring TB evaluation. In the intervention arm, CHWs obtained sputum from 35/91 (39%) of sputum-eligible contacts and SMSs were sent to 95/190 (50%). Completion of TB evaluation in the intervention and standard-of-care arms at 14 days (14% versus 15%; difference −1%, 95% CI −9% to 7%, p=0.81) and yields of confirmed TB (1.5% versus 1.1%, p=0.62) and new HIV (2.0% versus 1.8%, p=0.90) diagnoses were similar. Conclusions: Home-based, SMS-facilitated evaluation did not improve completion or yield of household TB contact investigation, likely due to challenges delivering the intervention components. In a household randomised trial in Kampala, Uganda, home-based, SMS-facilitated evaluation did not improve completion or yield of household TB contact investigation. Future studies will evaluate user-centred design to improve intervention delivery. http://bit.ly/2xwLpDu